PERANCANGAN SISTEM INFORMASI PENGELOLAAN ASET INVENTARIS DIVISI PARKIR MENGGUNAKAN QR CODE BERBASIS WEB (STUDI KASUS: UNIVERSITAS PAMULANG) - Mohamad Adriansyah; Entis Sutrisna (CV. Multi Kreasi Media, 2022)
Pamulang University is a private university located in the city of South Tangerang. In supporting academic activities, Pamulang University has work units to support the smooth running of academic activities, one of which is a parking work unit that functions to manage parking such as controlling vehicles entering or leaving computerized, and regulating traffic entering the parking building. Currently the parking division does not yet have an internal information system to manage and control assets owned so that in operational implementation when officers want to know the number and status of asset conditions, it is still done by looking at and calculating the physical parking assets directly which takes a long time due to the number of assets needed. lots on each location like viktor, witana, and stikes. Based on these problems, the researcher intends to create an INVENTORY ASSET MANAGEMENT INFORMATION SYSTEM PARKING DIVISION USING A COMPUTERIZED WEB-BASED QR CODE to simplify and speed up the process of checking conditions with a QR Code, knowing the number of assets entering or leaving so that the system built is expected to provide fast and accurate information. This information system was developed using the PHP programming language and MySOL database with the development method using the Waterfall model.